OPTIMALISASI HASIL AFKIR PERKEBUNAN JAMBU KRISTAL MENJADI MANISAN BASAH DI DUSUN NGINGAS - Miracle Drew Hansel Hartanto; Nanda Oktavia; Amalia Rosida Fajriyah; Nurida Tri Novita; Maulia Widi; Anugerah Dany Priyanto (Journal of Science and Social Development, 2019)
Candied food is one of the foods favored by the community so that many fruits are often processed into sweets. Making sweets is usually by using fresh fruits. Ngingas Hamlet is an area whose livelihood is cultivated. There are gardens that are planted with crystal guava fruit, which every time there are harvested cashew nuts. These problems have become challenges as well as opportunities for training related to the use of cashew fruit in Ngingas Hamlet, Prambon District, Sidoarjo. The purpose of this activity is to improve the ability of PKK mothers so that the rejected crop yields can be utilized and have selling value. The implementation was carried out with several activities, namely location surveys, training, and monitoring. The implementation method used is the procurement of materials, sweets, and monitoring and evaluation. The results of the implementation achieved are the increasing ability of PKK Ngingas hamlets to process crystal rejects into candied products. The creation of new innovative products for refined crystal guava candies is worth selling.